Analytic methods in systems and software testing - Kenett, Ron; Ruggeri, Fabrizio; Faltin, Frederick W. (John Wiley & Sons, Inc., 2018)
A comprehensive treatment of systems and software testing using state of the art methods and tools, this book uses numerous examples to provide an understanding in applying these methods to real-world problems. --